Comparing interglacials in eastern Australia: A multi-proxy investigation of a new sedimentary record. (15th January 2021) - Forbes, Matt; Cohen, Tim; Jacobs, Zenobia; Marx, Sam; Barber, Emily; Dodson, John; Zamora, Andrés; Cadd, Haidee; Francke, Alexander; Constantine, Mark; Mooney, Scott; Short, Julia; et al.
Abstract: The widespread formation of organic rich sediments in south-east Australia during the Holocene (Marine Isotope Stage [MIS] 1) reflects the return of wetter and warmer climates following the Last Glacial Maximum (LGM). Yet, little is known about whether a similar event occurred in the region during the previous interglacial (MIS 5e). A 6.8 m sediment core (#LC2) from the now ephemeral Lake Couridjah, Greater Blue Mountains World Heritage Area, Australia, provides insight into this question. Organic rich sediments associated with both MIS 1 and 5e are identified using 14 C and optically stimulated luminescence (OSL) dating techniques. Also apparent are less organic sedimentary units representing MIS 6, 5d and 2 and a large depositional hiatus. Sediment δ 13 C values (−34 to −26‰) suggests that C3 vegetation dominates the organic matter source through the entire sequence. The pollen record highlights the prevalence of sclerophyll trees and shrubs, with local hydrological changes driving variations in the abundance of aquatic and lake-margin species. The upper Holocene sediment (0–1.7 m) is rich in organic matter, including high concentrations of total organic carbon (TOC; 20–40%), fine charcoal and macrophyte remains. These sediments are also characterised by a large proportion of epiphytic diatoms and a substantial biogenic component (chironomids and midges). These attributes, combined with low δ 13 C and δ 15 N values, and C:N ratios of approximately 20, indicate a stable peat system in a swamp like setting, under the modern/Holocene climate. In comparison, the lower organic rich unit (MIS 5e-d) has less TOC (5–10%), is relatively higher in δ 13 C and δ 15 N, and is devoid of macrophyte remains and biogenic material. Characterisation of the organic matter pool using 13 C-NMR spectroscopy identified a strong decomposition signal in the MIS 5e organic sediments relative to MIS 1. Thus the observed shifts in δ 13 C, δ 15 N and C:N data between the two periods reflects changes in the organic matter pool, driven by decompositional processes, rather than environmental conditions. Despite this, high proportions of aquatic pollen taxa and planktonic diatoms in the MIS 5e–d deposits, and their absence in the Holocene indicates that last interglacial Lake Couridjah was deeper and, or, had more permanent water, than the current one. Highlights: New lacustrine sedimentary record for eastern Australia that encompasses the last glacial cycle. Evidence in the record of wet conditions linked to last two interglacials. Multi-proxy investigation of environmental conditions across the last glacial cycle. Novel investigations of soil organic matter (SOM) disentangling decomposition and environmental signatures. Robust chronological record identifying large depositional hiatus during MIS 4 and 3.